The relationship between aspects of socio-economic factors and academic achievement - Zahyah Hanafi, (penerbit ukm, 2008)
This study focused on two aspects of family socio-economy, that is, mother’s and father’s educational level and reading materials in the home. Four-hundred thirty form five students from three secondary schools in a district in Kedah were involved in this case study. The findings of this study support previous studies where both parents’ level of education and reading materials available in the home were related to children’s academic achievement. Findings are discussed and suggestions for further study are forwarded.